Implementation Intention and Action Planning Interventions in Health Contexts: State of the Research and Proposals for the Way Forward - Hagger, Martin; Luszczynska, A. (Wiley-Blackwell Publishing Ltd., 2014)
The purpose of this paper is to provide an overview of the literature on two planning intervention techniques in health behaviour research, implementation intentions and action planning, and to develop evidence-based recommendations for effective future interventions and highlight priority areas for future research. We focused our review on four key areas: (1) definition and conceptualisation; (2) format and measurement; (3) mechanisms and processes; and (4) design issues. Overall, evidence supports the effectiveness of planning interventions in health behaviour with advantages including low cost and response burden. There is, however, considerable heterogeneity in the effects across studies and relatively few registered randomised trials that include objective behavioural measures. Optimally effective planning interventions should adopt “if–then” plans, account for salient and relevant cues, include examples of cues, be guided rather than user-defined, and include boosters. Future studies should adopt randomised controlled designs, report study protocols, include fidelity checks and relevant comparison groups, and adopt long-term behavioural follow-up measures. Priority areas for future research include the identification of the moderators and mediators of planning intervention effects. Future research also needs to adopt “best practice” components of planning interventions more consistently to elucidate the mechanisms and processes involved.